MODEL BAHAN AJAR BAHASA INDONESIA YANG IDEAL DAN INOVATIF - Mesa Arruan, Yemima; Sukmawati; Abdul Haliq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is very important and an inseparable part of human life's journey. Through education, the quality of human resources can be increased by improving the education they receive. These qualities are important to participate in global life and live a fulfilling life. In Indonesia too, education is undergoing various changes which are reflected in the school curriculum with the reason that ``the curriculum needs to be replaced because it is not in line with current developments,'' and innovation is needed. Overall, the aim of this article is to describe an ideal and innovative model of Indonesian language teaching materials. The research results obtained show that in creating innovative teaching materials, educators need to know the factors that can support the success of the learning process, including knowledge about the teaching materials.